Description of the NIF Laser. (1st February 2016) - Spaeth, M. L.; Manes, K. R.; Kalantar, D. H.; Miller, P. E.; Heebner, J. E.; Bliss, E. S.; Spec, D. R.; Parham, T. G.; Whitman, P. K.; Wegner, P. J.; Baisden, P. A.; Menapace, J. A.; et al.
Abstract: The possibility of imploding small capsules to produce mini-fusion explosions was explored soon after the first thermonuclear explosions in the early 1950s. Various technologies have been pursued to achieve the focused power and energy required for laboratory-scale fusion. Each technology has its own challenges. For example, electron and ion beams can deliver the large amounts of energy but must contend with Coulomb repulsion forces that make focusing these beams a daunting challenge. The demonstration of the first laser in 1960 provided a new option. Energy from laser beams can be focused and deposited within a small volume; the challenge became whether a practical laser system can be constructed that delivers the power and energy required while meeting all other demands for achieving a high-density, symmetric implosion. The National Ignition Facility (NIF) is the laser designed and built to meet the challenges for study of high-energy-density physics and inertial confinement fusion (ICF) implosions. This paper describes the architecture, systems, and subsystems of NIF. It describes how they partner with each other to meet these new, complex demands and describes how laser science and technology were woven together to bring NIF into reality.